Information Science: The Canadian Context - Wolfram, Dietmar; Chu, Clara (Scientia Canadensis, 1989)
ABSTRACTThis study outlines the development of information science in Canada through an examination of the research contributions to the field by Canadians. Identification of contributors, their backgrounds and the sub-areas of information science to which they have contributed indicate that the field continues to draw inter-disciplinary contributions from a wide variety of academic fields. Despite the tenuous self-identity of the discipline, the development of Canadian periodicals as well as undergraduate and graduate education programmes devoted to information science indicate an increased recognition of the existence and validity of the discipline.